2015
DOI: 10.4274/tjod.93546
|View full text |Cite
|
Sign up to set email alerts
|

Should we add unilateral sacrospinous ligament fixation to vaginal hysterectomy in management of stage 3 and stage 4 pelvic organ prolapse?

Abstract: Objective:To compare ‘‘vaginal hysterectomy alone’’ with ‘‘vaginal hysterectomy with prophylactic unilateral sacrospinous ligament fixation’’ in terms of intraoperative complications and 1-year anatomic outcomes and symptoms in patients aged over 50 years who presented with stage 3 or 4 pelvic organ prolapse (POP).Materials and Methods:Thirty-five patients underwent vaginal hysterectomy alone and 32 patients underwent vaginal hysterectomy with unilateral sacrospinous ligament fixation because of benign patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Our incidence was comparable to studies by Guner et al and Elif et al who reported 18% and 21.9% incidence of gluteal pain and nerve injury. 11,14 If the pain is severe or associated with paresthesia, reoperation and relocation of the suture more medially are often suggested but in our study the pain was transient and subsided within 7 to 30 days of surgery by analgesics and anti-inflammatory agents. 7 Colombo and Milani compared SLF with McCall culdoplasty and found that the latter yielded better results in terms of length of operation, blood loss as approaching the sacrospinous ligament requires additional tissue dissection which is not the case in McCall culdoplasty.…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…Our incidence was comparable to studies by Guner et al and Elif et al who reported 18% and 21.9% incidence of gluteal pain and nerve injury. 11,14 If the pain is severe or associated with paresthesia, reoperation and relocation of the suture more medially are often suggested but in our study the pain was transient and subsided within 7 to 30 days of surgery by analgesics and anti-inflammatory agents. 7 Colombo and Milani compared SLF with McCall culdoplasty and found that the latter yielded better results in terms of length of operation, blood loss as approaching the sacrospinous ligament requires additional tissue dissection which is not the case in McCall culdoplasty.…”
Section: Resultscontrasting
confidence: 50%
“…Elif et al reported a similar incidence of 18.8%. 11 However, incidence reported by Gupta et al and Hefani et al was 1.9% and 1.8% respectively. 12,13 Statistically significant complication that was noted post operatively within one week of surgery was gluteal pain, which was more common in the SSLF group-7 (16.28%).…”
Section: Resultsmentioning
confidence: 92%
“…It has been also shown that unilateral SSLF prophylactic to vaginal hysterectomy may reduce the recurrence rates in patients with stage3-4 POP 31 . In our study, although there was a significant difference between the unilateral and bilateral SSLF in terms of the operation time and amount of bleeding, these complications did not cause any additional morbidity.…”
Section: Discussionmentioning
confidence: 98%
“…Correction of apical prolapse is especially important in POP surgery to prevent future vaginal cuff prolapse [24]. Uterosacral ligament suspension, SSLF, abdominal open and laparoscopic sacral colpopexy are mainly utilized surgical procedures to support the vaginal apex [11,18]. Each of these procedures carries their own benefits and risks.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with POP in whom a VAH is planned, the addition of sacrospinous ligament fixation (SSLF) procedure might decrease the rate of postoperative vaginal cuff prolapse [12,13]. However, the addition of this procedure might also increase the operative time and the risk of perioperative complications [14][15][16][17][18]. The purpose of the present study was to determine the risk of de novo SUI occurrence in women who were treated with SSLF in addition to VAH and colporrhaphy anterior-posterior (VAH + CAP) over a follow-up period of 24 months.…”
Section: Introductionmentioning
confidence: 99%